A droplet digital PCR (ddPCR) assay to detect Helicoverpa armigera (Lepidoptera: Noctuidae) in bulk trap samples - Zink, Frida A. (PLoS One, 2017)
Moths in the genus Helicoverpa are some of the most important agricultural pests in the world. Two species, H. armigera (Hübner) and H. zea (Boddie), cause the majority of damage to crops and millions of dollars are spent annually on control of these pests. The recent introduction of H. armigera into the New World has prompted extensive survey efforts for this species in the United States. Surveys are conducted using bucket traps baited with H. armigera pheromone, and, because the same pheromone compounds attract both species, these traps often capture large numbers of the native H. zea. Adult H. armigera and H. zea are very similar and can only be separated morphologically by minor differences in the genitalia. Thus, a time consuming genitalic dissection by a trained specialist is necessary to reliably identify either species, and every specimen must be dissected. Several molecular methods are available for differentiating and identifying H. armigera and H. zea, including two recently developed rapid protocols using real-time PCR. However, none of the published methods are capable of screening specimens in large batches. Here we detail a droplet digital PCR (ddPCR) assay that is capable of detecting a single H. armigera in a background of up to 999 H. zea. The assay has been tested using bulk extractions of 1,000 legs from actual trap samples and is effective even when using poor quality samples. This study provides an efficient, rapid, reproducible, and scalable method for processing H. armigera survey trap samples in the U.S. and demonstrates the potential for applying ddPCR technology to screen and diagnose invasive species.